Membangun Karakter Masyarakat Bangsa Berbasis Teologi Gerakan Spiritual Baru - T. Safir Iskandar (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
The ideas for change can not be separated from the culture and civilization that  originated from the paradigm that produces new creativities when faced with social stagnation.  To solve the social problems, the sociological imagination ideas that exist and develop in the  society should be incorporated so that they become a theological value system from the  personal integrity of a community of nation. It is now the time for social imagination, as an  idea, to be raised by an awareness to create and stimulate various changes in collective  articulated discourses that deny the realities of social inequality established by the hegemony  of any interests in the form of weakening the integrity of the nation in the name of the state.  Theologically, for a successful and sustainable development of the nation there are six things  to be considered: first, put the truth as the purpose of life. Second, the community of nations  should not be restrained or restrain themselves both in thought and in social expression to the  extent not contrary to the universal values. Third, justice must be incorporated into all aspects  of society. Fourth, education must be provided to everyone. Fifth, critical thinking must be  nurtured to respond to everything that goes into the community of nation both from within and  from outside. And the last is the consistency and sincerity, dependability and sustainability of  the five points mentioned above.